Augmented formic acid electro-oxidation at a co-electrodeposited Pd/Au nanoparticle catalyst - Yaser M. Asal; Ahmad M. Mohammad; Sayed S. Abd El Rehim; Islam M. Al-Akraa (Journal of Saudi Chemical Society)
In this study, the formic acid electro-oxidation reaction (FAEOR) was catalyzed on a Pd-Au co-electrodeposited binary catalyst. The kinetics of FAEOR were intensively impacted by changing the Pd2+:Au3+ molar ratio in the deposition medium. The Pd1-Au1 catalyst (for which the Pd2+:Au3+ molar ratio was 1:1) acquired the highest activity with a peak current density for the direct FAEOR (Ip) of 4.14 mA cm−2 (ca. 13- times higher than that (ca. 0.33 mA cm−2) of the pristine Pd1-Au0 catalyst). It also retained the highest stability that was denoted in fulfilling ca. 0.292 mA cm−2 (ca. 19-times higher than 0.015 mA cm−2 of the pristine Pd1-Au0 catalyst) after 3600 s of continuous electrolysis at 0.05 V. The CO stripping and impedance measurements confirmed, respectively, the geometrical and electronic enhancements in the proposed catalyst.